Value for Money Perception on Buying Intention Halal Cosmetics: Mediated by Emotional Brand Attachment - Hafidza Gumelar Muksininna; Ririn Tri Ratnasari (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini bertujuan untuk mengetahui adanya pengaruh value for money perception dan emotional brand attachment terhadap niat membeli kosmetik halal khususnya produk Innisfree. Selain itu, untuk meningkatkan literasi tentang value for money perception dan emotional brand attachment terhadap buying intention. Pendekatan kuantitatif digunakan dalam metodologi penelitian ini dengan Path Analysis sebagai teknik analisis data. Pengumpulan data dengan menyebarkan kuesioner skala Likert berskala lima secara online. Responden dalam penelitian ini adalah 100 mahasiswi diberbagai universitas di Surabaya yang belum pernah menggunakan produk Innisfree. Hasil dari riset menunjukkan bahwa hubungan antar variabel value for money perception terhadap buying intention, value for money perception terhadap emotional brand attachment, dan emotional brand attachment terhadap buying intention ketiganya memiliki pengaruh secara signifikan positif. Kata Kunci: Value for Money Perception, Emotional Brand Attachment, Buying Intention, Kosmetik Halal. ABSTRACT This study aims to determine the effect of value for money perception and emotional brand attachment on the intention to buy halal cosmetics, especially Innisfree products. In addition, to increase literacy about value for money perception and emotional brand attachment to buying intention. A quantitative approach is used in this research methodology with Path Analysis as a data analysis technique. Collecting data by distributing a five-scale Likert scale questionnaire online. Respondents in this study were 100 female students in various universities in Surabaya who had never used Innisfree products. The results of the research show that the relationship between the variable value for money perception on buying intention, value for money perception on emotional brand attachment, and emotional brand attachment on buying intention, all three have a significant positive effect. Keywoards: Value for Money Perception, Emotional Brand Attachment, Buying Intention, Halal Cosmetics. DAFTAR PUSTAKA Alnawas, I., & Hemsley-Brown, J. (2018). The differential effect of cognitive and emotional elements of experience quality on the customer-service provider’s relationship. International Journal of Retail & Distribution Management, 46(2), 125–147. Aw, E. C., Chuah, S. H., & Fazli, M. (2021). Go loud or go home ? How power distance belief influences the effect of brand prominence on luxury goods purchase intention. Journal of Retailing and Consumer Services, 58(September 2020), 102288. https://doi.org/10.1016/j.jretconser.2020.102288 Briliana, V., & Mursito, N. (2017). Exploring antecedents and consequences of Indonesian Muslim youths' attitude towards halal cosmetic products: A case study in Jakarta. Asia Pacific Management Review, 22(4), 176-184. Budiyono, B. S., & Ratnasari, R. T. (2020). Determinants factors of hindus customers in using bank muamalat service. Hamdard Islamicus, 43(1), 212–230. Butcher, L., Phau, L., Teah, M. (2016). Brand prominence in luxury consumption: will emotional value adjudicate our longing for status? Journal of. Brand Management. 23 (6), 701–715. Cardinale, S., Nguyen, B., & Melewar, T. (2015). place-based brand experience, place attachment and loyalty. Marketing Intelligence & Planning, 33(3), 238–257. Casteran, G., & Ruspil, T. (2021). How can an organic label help a private label? Journal of Consumer Marketing, 2(December 2020), 191–200. https://doi.org/10.1108/JCM-08-2019-3374. Chae, H., Kim, S., Lee, J., & Park, K. (2020). Impact of product characteristics of limited edition shoes on perceived value, brand trust, and purchase intention; focused on the scarcity message frequency. Journal of Business Research, 120(November), 398–406. https://doi.org/10.1016/j.jbusres.2019.11.040. Chand, V., & Fei, C. (2020). Self-brand connection and intention to purchase a counterfeit luxury brand in emerging economies. Journal of Consumer Behaviour, August, 1–13. https://doi.org/10.1002/cb.1871 Dabbous, A., & Barakat, K. Aoun. (2020). Bridging the online offline gap: Assessing the impact of brands’ social network content quality on brand awareness and purchase intention. Journal of Retailing and Consumer Services, 53(March 2019), 101966. https://doi.org/10.1016/j.jretconser.2019.101966 Dash, G., Kiefer, K., & Paul, J. (2021). Marketing-to-Millennials: Marketing 4.0, customer satisfaction and purchase intention. Journal of Business Research, 122(February 2020), 608–620. https://doi.org/10.1016/j.jbusres.2020.10.016 Dwivedi, A., Johnson, L. W., Wilkie, D. C., & Araujo-Gil, L. D. (2019). Consumer emotional brand attachment with social media brands and social media brand equity. European Journal of Marketing, 53(6), 1176–1204. https://www.emerald.com/insight/search?q=Emotional Fastoso, F., & González-Jiménez, H. (2020). Materialism, cosmopolitanism, and emotional brand attachment: The roles of ideal self-congruity and perceived brand globalness. Journal of Business Research, 121(December), 429–437. https://doi.org/10.1016/j.jbusres.2018.12.015 Hayati, A., & Ratnasari, R. T. (2020). Factors affecting muslim consumer decisions on choosing Islamic hotel. Hamdard Islamicus, 43(2), 619–638. Henry, A. (2001). Consumer Behaviour and Marketing Action. Singapore. Thomson Learning Innisfree. (2021). Konsep Brand Innisfree. Retrieved from innisfree.com Japutra, A., Ekinci, Y., & Simkin, L. (2019). Self-congruence, brand attachment and compulsive buying. Journal of Business Research, 99(August), 456–463. https://doi.org/10.1016/j.jbusres.2017.08.024 Kaufmann, H. R., Petrovici, D. A., Filho, C. G., & Ayres, A. (2016). Identifying moderators of brand attachment for driving customer purchase intention of original vs counterfeits of luxury brands. Journal of Business Research, 69(12), 5735–5747. https://doi.org/10.1016/j.jbusres.2016.05.003 Kementerian Agama RI. (2021). Al-Qur'an dan terjemahan. Retrieved from www.quran.kemenag.go.id Khalek, A. A., & Ismail, S. H. S. (2015). Why are we eating halal – Using the theory of planned behavior in predicting halal food consumption among generation Y in Malaysia. International Journal of Social Science and Humanity, 5(7), 608–612. https://doi.org/10.7763/ijssh.2015.v5.526 Kotler, P., & Amstrong, G. (2008). Prinsip-prinsip pemasaran. Jakarta: Erlangga Ku, T., & Lin, T. (2018). Effects of luxury brand perceptions on brand attachment and purchase intention: A comparative analysis among consumers in China, Hong Kong and Taiwan. South African Journal of Business Management, 49(1), 1–9. https://doi.org/10.4102/sajbm.v49i1.6 Li, G., Li, G., & Kambele, Z. (2012). Luxury fashion brand consumers in China: Perceived value, fashion lifestyle, and willingness to pay. Journal of Business Research, 65(10), 1516–1522. https://doi.org/10.1016/j.jbusres.2011.10.019 Lim, X., Cheah, J., Cham, T., Ting, H., & Memon, M. (2020). Compulsive buying of branded apparel, its antecedents, and the mediating role of brand attachment. Asia Pacific Journal of Marketing and Logistics, 32(7), 1539–1563. https://doi.org/10.1108/APJML-03-2019-0126 Liu, D., & Guo, X. (2017). Can trust and social benefit really help? Empirical examination of purchase intentions for wearable devices. Information Development, 33(1), 43–56. https://doi.org/10.1177/0266666916635724 Mattila, Anna, W. Y. (2016). Why do we buy luxury experiences? Measuring value perceptions of luxury hospitality services. International Journal of Contemporary Hospitality Management, 28(9), 1848-1867. https://doi.org/10.1108/IJCHM-11-2014-0579 Bappenas. (2018). Masterplan Ekonomi Syariah Indonesia 2019-2024. Kementerian Perencanaan Pembangunan Nasional/ Badan Perencanaan Pembangunan Nasional, 1–443 Nasution, M., & Yasin, H. (2014). Pengaruh promosi dan harga terhadap minat beli perumahan Obama PT. Nailah Adi Kurnia Sei Mencirim Medan. Jurnal Manajemen & Bisnis, 14(2), 135–143. http://dx.doi.org/10.30596%2Fjimb.v14i2.182 Nenycz-Thiel, M., & Romaniuk, J. (2012). Value-for-money perceptions of supermarket and private labels. Australasian Marketing Journal, 20(2), 171–177. https://doi.org/10.1016/j.ausmj.2011.12.002 Niros, M. I., & Pollalis, Y. A. (2011). Brand personality and consumer behavior: Strategies for building strong service brands. Journal of Marketing & Operations Management Research, 2(2), 101–115. Peterson, C., & Skolits, G. (2020). Value for money: A utilization-focused approach to extending the foundation and contribution of economic evaluation. Evaluation and Program Planning, 80(July 2018), 101799. https://doi.org/10.1016/j.evalprogplan.2020.101799 Pino, G., Amatulli, C., Peluso, A., Nataraajan, R., & Guido, G. (2019). Brand prominence and social status in luxury consumption: A comparison of emerging and mature markets. Journal of Retailing and Consumer Services, 46(November 2017), 163–172. https://doi.org/10.1016/j.jretconser.2017.11.006 Ratnasari, R. T., Ula, U. F., & Sukmana, R. (2020). Can store image moderate the influence of religiosity level on shopping orientation and customers’ behavior in Indonesia? Journal of Islamic Accounting and Business Research, 12(1), 78–96. https://doi.org/10.1108/JIABR-01-2017-0006 Sedianingsih, Ratnasari, R. T., Prasetyo, A., & Mawardi, I. (2018). Determinant of intention to check-up back to doctors at public hospital. International Journal of Engineering and Technology(UAE), 7(3), 31–32. https://doi.org/10.14419/ijet.v7i3.21.17088 Standard, D. (2019). State of the global Islamic economy report 2019/20. Dubai International Financial Centre, 1–174. Retrieved from https://haladinar.io/hdn/doc/report2018.pdf Suhartanto, D., Dean, D., Sarah, I. S., Hapsari, R., Amalia, F. A., & Suhaeni, T. (2020). Does religiosity matter for customer loyalty? Evidence from halal cosmetics. Journal of Islamic Marketing, 12(8), 1521-1534. https://doi.org/10.1108/JIMA-03-2020-0069 Suparno, C. (2020). Online purchase intention of halal cosmetics: S-O-R framework application. Journal of Islamic Marketing, 12(9), 1665-1681. https://doi.org/10.1108/JIMA-09-2019-0192 Thomas, T., & Johnson, J. (2017). The impact of celebrity expertise on advertising effectiveness: The mediating role of celebrity brand fit. Vision, 21(4), 367–374. https://doi.org/10.1177/0972262917733174 Vahdat, A., Hafezniya, H., Jabarzadeh, Y., & Thaichon, P. (2020). Emotional brand attachment and attitude toward brand extension. Services Marketing Quarterly, 41(3), 236-255. https://doi.org/10.1080/15332969.2020.1786245 Vredeveld, Anna J. (2018). Emotional intelligence, external emotional connections and brand attachment. Journal of Product and Brand Management, 27(5), 545–556. https://doi.org/10.1108/JPBM-10-2017-1613 Wu, B., & Yang, W. (2018). What do chinese consumers want? A value framework for luxury hotels in China. International Journal of Contemporary Hospitality Management, 30(4), 2037-2055. https://doi.org/10.1108/IJCHM-08-2016-0466 Zapclinic. (2018). Beauty index 2018. Retrieved from https://zapclinic.com/zapbeautyindex